2021
DOI: 10.3892/ol.2021.12747
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA UBAP2 promotes the proliferation of prostate cancer cells via the miR‑1244/MAP3K2 axis

Abstract: Prostate cancer (PCa) is a common male malignant disease with a high incidence, which can seriously affect the quality of life of patients. The survival rate of patients with PCa has improved to 98.6%; however, new insights for the molecular mechanism are still urgently required. Circular RNA (circ)UBAP2 is a tumor-associated circRNA that has been demonstrated to promote the progression of various types of cancer. CircUBAP2 has been demonstrated to be significantly upregulated in PCa, but its role in the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…circRNAs regulate the development and progression of many cancers, including PCa, and this has been confirmed by many studies 20,21 . Here, we confirmed that hsa_circ_0070512 was highly expressed in PCa tissues and cell lines, had a circular structure, and was resistant to RNase R. Functional assays showed that hsa_circ_0070512 facilitated the proliferation and migration of PCa cells.…”
Section: Discussionsupporting
confidence: 82%
“…circRNAs regulate the development and progression of many cancers, including PCa, and this has been confirmed by many studies 20,21 . Here, we confirmed that hsa_circ_0070512 was highly expressed in PCa tissues and cell lines, had a circular structure, and was resistant to RNase R. Functional assays showed that hsa_circ_0070512 facilitated the proliferation and migration of PCa cells.…”
Section: Discussionsupporting
confidence: 82%
“…Some of these circRNA host genes, such as KMT2C 40 , BRWD1 41 , 42 , and CHD2 43 , have been implicated in sperm function and male fertility. In addition, some of these host genes have been used as important prostate cancer marker genes, such as TRIM24 44 , UBAP2 45 , ULK4 46 , and SMARCC1 47 . Interestingly, we found that circRNAs derived from these host genes in SPEVs were also identified in sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Circ_0003945 have been associated with a variety of diseases, including various neoplasms and non-malignant conditions such as microcirculatory perfusion ( 44 , 45 ), diabetic retinopathy (DR) ( 35 ), osteoarthritis (OA) ( 46 ), preeclampsia (PE) ( 47 ), and milk fat metabolism ( 48 ). Noteworthy, circ_0003945 was highly overexpressed and linked to poor prognosis, including in glioma ( 49 ), thyroid cancer (TC) ( 36 ), esophageal cancer (EC) ( 50 ), non-small cell lung cancer (NSCLC) ( 51 ), breast cancer (BC) ( 34 ), hepatocellular carcinoma (HCC) ( 52 ), pancreatic cancer ( 53 ), colorectal cancer (CRC) ( 54 ), ovarian cancer (OC) ( 55 ), cervical cancer (CC) ( 56 ), prostate cancer ( 57 ), and osteosarcoma ( 58 ) ( Figure 3 ). However, it is noteworthy that the expression of circ_0003945 in gastric cancer (GC) ( 59 ) and renal cell carcinoma (RCC) ( 60 ) were lower compared to normal tissue, which also suggested a more favorable prognosis.…”
Section: Introductionmentioning
confidence: 99%